THE SPATIAL POLITICS OF MOSQUES: CONTESTED AUTHORITY AND PSYCHOLOGICAL SPLIT IN MAKASSAR’S POST-ISLAMIST URBAN SOCIETY: Spatial Manifestations and Psychological Split Among Muslims in the Post-Islamist Era - Awal Muqsith; Mubarak Taswin; Andi Aderus; Muhammad Zakir Husein (Al-Qalam, 2026)
This study investigates the paradoxical duality of urban mosques in Makassar, Indonesia, whichsimultaneously serve as centers of spiritual vitality and arenas of spatial and ideological contestation.We argue that this duality constitutes a spatial symptom of the collective psychological split amongMuslim societies in the post-Islamist era. By applying Asef Bayat's analytical category of postIslamism—in which political Islam's energy shifts toward socio-cultural piety rather than statecontrol—this study integrates it with Henri Lefebvre's theory of the production of space. The researchemploys a quantitative descriptive approach with qualitative-theoretical interpretation, utilizingsurvey data from 307 respondents across 13 sub-districts. The findings reveal a fundamental tension:while mosques demonstrate high congregational satisfaction, good management, and successfuladaptation to urban needs, they also exhibit a possessive logic of space. This logic manifests throughdense mosque proliferation, soundscape contestation, significant resistance to religious plurality,and persistent ideological contestation within mosque pulpits. These findings challenge the simplisticinterpretation of mosque abundance as mere collective piety, revealing instead a tension betweenpsychological fragmentation and collective struggles for spatial domination, both of whichundermine principles of inclusive citizenship